Professor Geoffrey Petts (1953–2018): An outstanding interdisciplinary river scientist. (7th November 2019) - Gurnell, Angela; Foster, Ian; Gregory, Ken; Wood, Paul
Abstract: This paper provides an introduction and an editorial to this special issue of River Research and Applications by documenting the contributions made by Professor Geoffrey Petts to our interdisciplinary understanding of the functioning of rivers and their floodplains and their sustainable management. We outline Geoff's career, which framed not only his research but its communication through his inspirational teaching but also included very high level and innovative contributions to the management and development of several UK universities. We then explain how and why Geoff was an outstanding interdisciplinary river scientist and how he communicated his science through both integrative books and book chapters and also research papers that developed eight complementary research themes. Lastly, we introduce the papers in this special issue and show how they provide inputs to Geoff's areas of research interest.